2019
DOI: 10.1108/ijmf-05-2019-0194
|View full text |Cite
|
Sign up to set email alerts
|

Timing the market with own stock: an extensive analysis with buying and selling evidence

Abstract: Purpose Are firms able to time the market? The purpose of this paper is to focus on the study of own stock trading, emphasizing both repurchase and resell operations on the open market as well as over the counter. Design/methodology/approach The authors use data on 37,997 own stock transactions from 2005 to 2015 of Euronext Lisbon listed firms. Following Dittmar and Field (2015), this paper uses relative transaction prices to ascertain the relative performance of own stock transactions, in the open market an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…This shows signs of market timing capabilities which are stronger when we look at a weekly time window. On the aggregate, when bridging insiders' results with firms own stock trading results studied by Santos and Gama (2019) as well as Dittmar and Field (2015), we verify that they go hand in hand in terms of performance, especially when looking at the buying activity. Interestingly and focusing on the selling, insiders even overperform firms as Santos and Gama (2019) show.…”
Section: Introductionsupporting
confidence: 72%
See 4 more Smart Citations
“…This shows signs of market timing capabilities which are stronger when we look at a weekly time window. On the aggregate, when bridging insiders' results with firms own stock trading results studied by Santos and Gama (2019) as well as Dittmar and Field (2015), we verify that they go hand in hand in terms of performance, especially when looking at the buying activity. Interestingly and focusing on the selling, insiders even overperform firms as Santos and Gama (2019) show.…”
Section: Introductionsupporting
confidence: 72%
“…When looking at the selling activity, with the exception of the short-term (intraday) window, where there is no evidence of over (or under) performance, we showcase that insiders are actually selling their stock at a relatively higher price when compared to other traders in the market. This is especially interesting if we compare with the results of Santos and Gama (2019) where the authors found that firms reselling own stock are not able to time the market, thus we show that insiders, when performing private trades, outperform even their own institutional trading activity which can suggest the use of privileged information to optimize their timing when compared to a corporate and third-party perspective.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations